Wound Pattern Profile in Deceased Victims of Traffic Accidents in Raden Said Sukanto Bhayangkara Hospital Jakarta from January 2017 until December 2018 - Evan Boedi Dewanto; Ahmad Yudianto; Magda Rosalina Hutagalung (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Highlights:1. Traffic accidents can cause different types of wounds.2. Traffic accident victims were predominantly male at the age of 26-45 years old. 3. The most found wounds were abrasions and the most affected area were head and neck. AbstractIntroduction: A traffic accident is an incident that happens on the road, such as a car crash that started on the road and leads to injury or death or damaged properties in the surrounding environment. Traffic accident injuries have a different pattern from any other events or violence, such as a mechanical injury due to friction with asphalt. The wounds that are usually found on the victims are abrasion, laceration, contusion, and wounds with fracture. About 70% of traffic accidents in Indonesia are happening in Java. The aim of this study was to determine the wound patterns of victims of traffic accidents, particularly deceased victims recorded in the Forensic Department of Raden Said Sukanto Bhayangkara Hospital Jakarta from January 2017 until December 2018.Methods: This was a descriptive study using secondary data. Consecutive sampling methods were used by using an external examination form obtained from the Forensic Department of Raden Said Sukanto Bhayangkara Hospital Jakarta from January 2017 until December 2018. Age, gender, and wound patterns such as abrasion, laceration, contusion, and wounds with fracture data were taken.Results: 67 cases of traffic accidents were recorded. Male victims were the most common victims (87.5%) within the age of 26–45 years old (42.18%). Abrasions were the most common wounds found (44.92%) and head and neck region were the most affected area (44.09%).Conclusion: The deceased victims of traffic accidents were mostly males aged 26–45 years old. The most common wound found were abrasions and the most affected areas were head and neck region.